2020
DOI: 10.1101/2020.06.11.20128686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitivity of commercial Anti-SARS-CoV-2 serological assays in a high-prevalence setting

Abstract: We analysed SARS-CoV-2 specific antibody responses in 42 social and working contacts of a super-spreader from the Heinsberg area in Germany. Consistent with a high-prevalence setting 26 individuals had SARS-CoV-2 antibodies determined by in-house neutralisation testing. These results were compared with four commercial assays, suggesting limited sensitivity of the assays in such a high-prevalence setting. Although SARS-CoV-2 nucleocapsid restricted tests showed a better sensitivity, spike based assays had a str… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
0
22
0
2
Order By: Relevance
“…However, it should be noted that the PNA reported herein is based on only two isolates and thus requires further validation. These findings are in overall agreement with those of Müller et al, who compared four commercially available serological assays for SARS-CoV-2 (the Elecsys Anti-SARS-CoV-2 immunoassay, EuroImmun anti-SARS-CoV-2 IgA and IgG enzyme-linked immunosorbent assay [ELISA], Abbott SARS-CoV-2 IgG chemiluminescent microparticle immunoassay [CMIA], and Liaison SARS-CoV-2 S1/S2 IgG chemiluminescent immunoassay [CLIA]) with a neutralization assay and observed good PPA (65.4%), PNA (100%), and POA (78.6%) for the Elecsys Anti-SARS-CoV-2 immunoassay ( 23 ). Our results also align with those of Kohmer et al, who compared six commercially available serological assays for SARS-CoV-2 (the Elecsys Anti-SARS-CoV-2 immunoassay, EuroImmun anti-SARS-CoV-2 IgG ELISA, Abbott SARS-CoV-2 IgG CMIA, Liaison SARS-CoV-2 S1/S2 IgG CLIA, VirClia COVID-19 IgG Monotest CLIA, and Virotech SARS-CoV-2 IgG ELISA) with an in-house plaque reduction neutralization test and observed good PPA (75.6%), PNA (97.1%), and POA (84.8%) ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that the PNA reported herein is based on only two isolates and thus requires further validation. These findings are in overall agreement with those of Müller et al, who compared four commercially available serological assays for SARS-CoV-2 (the Elecsys Anti-SARS-CoV-2 immunoassay, EuroImmun anti-SARS-CoV-2 IgA and IgG enzyme-linked immunosorbent assay [ELISA], Abbott SARS-CoV-2 IgG chemiluminescent microparticle immunoassay [CMIA], and Liaison SARS-CoV-2 S1/S2 IgG chemiluminescent immunoassay [CLIA]) with a neutralization assay and observed good PPA (65.4%), PNA (100%), and POA (78.6%) for the Elecsys Anti-SARS-CoV-2 immunoassay ( 23 ). Our results also align with those of Kohmer et al, who compared six commercially available serological assays for SARS-CoV-2 (the Elecsys Anti-SARS-CoV-2 immunoassay, EuroImmun anti-SARS-CoV-2 IgG ELISA, Abbott SARS-CoV-2 IgG CMIA, Liaison SARS-CoV-2 S1/S2 IgG CLIA, VirClia COVID-19 IgG Monotest CLIA, and Virotech SARS-CoV-2 IgG ELISA) with an in-house plaque reduction neutralization test and observed good PPA (75.6%), PNA (97.1%), and POA (84.8%) ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…High-affinity nAbs are critical for the control of infection, since they can recognize and bind to specific viral epitopes, thereby "neutralizing" the virus and rendering it nonpathogenic (20,22). Previous studies involving commercially available anti-SARS-CoV-2 immunoassays have found a positive correlation between antibody titration results from pseudoneutralization assays and SARS-CoV-2 nAbs; however, further investigation is warranted (23,24).…”
mentioning
confidence: 99%
“…These are standard methods for coronavirus serology in blood serum 105 , 106 and can function as reference methods to evaluate the diagnostic performance of binding antibody tests. 107 Plaque reduction neutralization tests (PRNT) take advantage of virus–antibody interactions in a test tube or microtiter plate to measure antibody effects on viral infectivity in virus-susceptible cells. Briefly, serial dilutions of serum sample or antibody solution to be tested are incubated with a standardized amount of virus.…”
Section: Antibody Testsmentioning
confidence: 99%
“…For the detection of IgG isotype antibodies, our data suggest that the use of the S protein should be su cient to identify positive patients. However, there is evidence that the use of the S1 domain instead of the full-length S protein leads to less cross-reactivity [21] .…”
Section: Discussionmentioning
confidence: 99%